2020
DOI: 10.3390/su12176852
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of UV Filters in Mytilus galloprovincialis: Preliminary Data on the Acute Effects Induced by Environmentally Relevant Concentrations

Abstract: Ultraviolet (UV) filters are present in a broad range of personal hygiene products, which may be transported via aquatic environments and domestic wastewaters due to inefficient treating station sewage removal and direct human contact. The aim of the present study was to evaluate the potential effects of a UV filter, in particular benzophenone-3 (BP3) (also known as oxybenzone) on the mussel species Mytilus galloprovincialis. Mussels were exposed to this organic substance for 96 h in environmentally relevant c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“…Considering these results, a high concentration of UV-filters (such as OC) can provoke a suppression of the phase I enzyme activity; thus, activation was observed later during the post-exposure time. This suppression of enzyme activity was also observed during the metabolization of organic compounds in M. galloprovincialis exposed to higher concentrations of BP-3 (1 µg·L −1 ) (Bordalo et al 2020 ).…”
Section: Resultsmentioning
confidence: 57%
See 1 more Smart Citation
“…Considering these results, a high concentration of UV-filters (such as OC) can provoke a suppression of the phase I enzyme activity; thus, activation was observed later during the post-exposure time. This suppression of enzyme activity was also observed during the metabolization of organic compounds in M. galloprovincialis exposed to higher concentrations of BP-3 (1 µg·L −1 ) (Bordalo et al 2020 ).…”
Section: Resultsmentioning
confidence: 57%
“…Studies have revealed BP-3 and OC can alter endocrine or reproduction endpoints in fish ( Oncorhynchus mykiss , Oryzias latipes , and Danio rerio ), inducing estrogenic effects (Blüthgen et al 2014 ; Coronado et al 2008 ; Kim and Choi 2014 ; Kinnberg et al 2015 ; Kunz et al 2006 ; Rodríguez-Fuentes et al 2015 ). Furthermore, they may also induce oxidative stress, activation of biotransformation enzymes, and lipid peroxidation in bivalves (Bordalo et al 2020 ; Chaves Lopes et al 2020 ; O’Donovan et al 2020 ; Sendra et al 2017 ; Seoane et al 2021 ). Mutagenic and genotoxic responses have also been found under exposure to BP-3 and OC (Cuquerella et al 2012 ; Nakajima et al 2006 ).…”
Section: Introductionmentioning
confidence: 99%
“…The effect of the skin barrier on the human body is very important. The skin barrier protects our skin from the outside world, boosts our immunity, and we know that in today's epidemic situation, we must do our part more, this is shown in Figure 2 35,36 …”
Section: Resultsmentioning
confidence: 99%
“…The skin barrier protects our skin from the outside world, boosts our immunity, and we know that in today's epidemic situation, we must do our part more, this is shown in Figure 2. 35,36 Face-oriented cosmetics are being used all over the body, occupying a deep place in our lives. First, it is a language that was created when cosmetics companies emphasized moisture cosmetics, and it is a very important part to protect the skin from bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…The impact that sunscreen agents could have in organisms is relevant, namely in marine organisms. Recently, several studies revealed the dangerous and noxious effects of UV filters towards diverse aquatic species, such as mussels [ 14 , 52 , 53 ], algae [ 54 ], crustaceans [ 55 ], corals [ 56 , 57 , 58 , 59 ], sea urchins [ 16 ], fish [ 60 , 61 , 62 ], and even in dolphins [ 63 ]. There are two ways of studying the toxicological effects in marine organisms: by determining the concentration of UV filters in a specific organism, by collecting the marine organism in the environment, or through the organism’s exposure to a specific range of UV filters’ concentrations and subsequently verifying the effects [ 17 ].…”
Section: Challengesmentioning
confidence: 99%